Analysis of Cement Distribution Strategy Through Competitive Strategy and Distribution Channels with Innovation Strategy as Intervening at PT. Solusi Bangun Indonesia (PT. SBI ) Narogong Plant - Muhamad Henry Fasha; Titing Widyastuti (Yayasan Amerta Insan Unggul, 2024)
This study analyzes the effect of competitive strategy and distribution channels on the cement distribution strategy of PT. Solusi Bangun Indonesia (SBI) Narogong Plant, with innovation serving as an intervening variable. The research adopts a quantitative approach using primary data collected through questionnaires distributed to 93 managers at the Narogong Plant in Bogor Regency. Data analysis was performed using the Smart PLS 3.0 software to test both measurement and structural models. The results reveal that competitive strategy and distribution channels have a positive and significant influence on cement distribution strategy. Furthermore, both variables significantly affect innovation, which in turn has a positive effect on the distribution strategy. Innovation mediates the indirect influence of competitive strategy and distribution channels on cement distribution, indicating its essential role in enhancing distribution efficiency. The findings demonstrate that innovation-based competitiveness strengthens the company’s ability to adapt to market fluctuations, optimize delivery routes, and reduce operational costs. The high R-square values (0.886 for distribution strategy and 0.746 for innovation) indicate strong model reliability. Overall, this study provides managerial insights for PT. SBI in implementing innovation-driven strategies to improve operational efficiency and maintain sustainable competitiveness in Indonesia’s cement industry, where production capacity continues to exceed domestic consumption.